Patriots for Profit : Contractors and the Military in U.S. National Security. - Bruneau, Thomas (Stanford University Press, 2011)
This book develops a new approach to the analysis of civil-military relations by focusing on the effectiveness of the armed forces in fulfilling roles & missions, and on their efficiency in terms of cost. The approach is applied to the United States using official documents and interviews with policy-makers. In addition to analyzing the impact of defense reform initiatives over the past thirty years, the book includes the recent phenomenon of "contracting-out" security that has resulted in greater numbers of contractors in Iraq and Afghanistan than uniformed military personnel. While the book